Comparative analysis of plasma total antioxidant capacity in patients with hyperglycemia and hyperglycemia plus dyslipidemia. Issue 1 (January 2019) - Vichaibun, Virun; Khananurak, Kamonwan; Sophonnithiprasert, Thanet
Abstract: Aims: The aim of this study was to measure plasma total antioxidant capacity (TAC) level and superoxide dismutase (SOD) activity in order to assess the oxidative stress status and the antioxidant defense system in patients with hyperglycemia and both hyperglycemia and dyslipidemia. Materials and methods: Sixty blood samples of hyperglycemia, 60 blood samples of both hyperglycemia and dyslipidemia and 60 blood samples of normoglycemia and normolipidemia (controls) were collected into study. All samples were measured for the levels of plasma TAC and SOD by colorimetric method using microtiter-plate reader. Results: Plasma TAC significantly decreased in patients with hyperglycemia (0.42 ± 0.1 mM) and both hyperglycemia and dyslipidemia 0.41 ± 0.1 mM) compared to those of controls (0.47 ± 0.14) ( P  < 0.05), whereas plasma SOD significantly increased in patients with hyperglycemia (81.0 ± 17.9 U/ml) and both hyperglycemia and dyslipidemia (83.7 ± 21.3 U/ml) compared to those of controls (73.7 ± 17.4 U/ml) ( P  < 0.05). However, the levels of plasma TAC and SOD had no significant difference between patients with hyperglycemia and both hyperglycemia and dyslipidemia ( P  > 0.05). Conclusions: The present study showed the significant difference of plasma TAC and SOD levels in hyperglycemic patients with and without dyslipidemia compared to those of controls. There was no additive or synergistic effect in terms of decreased plasma TAC levels and elevated SOD activities between hyperglycemic patients with and without dyslipidemia.